Synergistic sensing of stratified structures enhancing touch recognition for multifunctional interactive electronics - Liao, Xinqin (2020)
Efficient touch feedback, capable of monitoring the magnitude of force and identifying active location, is significant to artificial intelligence and interactive robotics. It generally needs the integration of multitudinous sensing elements and intricate manufacturing procedures. Here we propose a multifunctional paper-based touch sensor to realize touch trajectory recognition as well as achieve pressure information. The asymmetric and symmetric structures are designed to skillfully construct localization layer and pressure sensing layer. These functional layers effectively assemble a scalable touch sensor and, thus, greatly simplify the device's architecture with the competitive advantages of easiness in fabrication, cost-effectiveness, self-switching characteristic, and programmability in interactive function. Through coding and using the electrical signals, human-computer interaction, human-machine interaction, and force-enhanced cryptographic matrix are explored and demonstrate the feasibility of the proposed touch sensor. This work provides a novel mechanosensational sensing paradigm to leverage the complex physics of a feasible strategy for advancing human-related interactive electronics.